Internet addiction and performance of health science students - Bhushan, Shashi; Piplani, Shobhit; Tekkalaki, Bheemsain V. (International Journal Of Community Medicine And Public Health, 2018)
Background: The unmonitored surge in the usage of Internet recently has led to Internet Addiction. Internet is a classical instrument known to stimulate addictive behaviour which is on the verge of developing into a considerable public health emergency in the future in a densely populated country like India. Adolescents are more susceptible to this as they spend more time browsing the web. This cross sectional study intends to find out the co-morbidities associated with Internet Addiction in students of health sciences in India. Methods: The study was conducted in an Indian Medical and Dental College. 900 students were randomly selected to fill up the questionnaire. 618 students fulfilled the selection criteria. Young’s Internet Addiction Test was used for assessing the prevalence of Internet Addiction. The Rosenberg self-esteem scale was used to measure the self-esteem. Results: 19.5% students were not addicted to Internet. 61% of students were mildly addicted while 19.5% students were moderately addicted. Significant association was found between academic performance and Internet Addiction. Also, Internet Addiction had no significant association with Self- Esteem and Obesity. Conclusions: Proper screening methods should be used for prompt detection and management of Internet Addiction and awareness should be made about the same. It should be given more attention and students should be made to understand about healthy and safe practices to use internet. There is a need of an improved questionnaire which can provide us better understanding of internet usage by people in terms of amount of time and purpose of using the internet.